An update on risk factors for cartilage loss in knee osteoarthritis assessed using MRI-based semiquantitative grading methods - Alizai, Hamza; Roemer, Frank; Hayashi, Daichi; Crema, Michel D.; Felson, David T.; Guermazi, Ali (European Radiology, 2015)
Arthroscopy-based semiquantitative scoring systems such as Outerbridge and Noyes' scores were the first to be developed for the purpose of grading cartilage defects. As magnetic resonance imaging (MRI) became available for evaluation of the osteoarthritic knee joint, these systems were adapted for use with MRI. Later on, grading methods such as the Whole Organ Magnetic Resonance Score, the Boston-Leeds Osteoarthritis Knee Score and the MRI Osteoarthritis Knee Score were designed specifically for performing whole-organ assessment of the knee joint structures, including cartilage. Cartilage grades on MRI obtained with these scoring systems represent optimal outcome measures for longitudinal studies, and are designed to enhance understanding of the knee osteoarthritis disease process. The purpose of this narrative review is to describe cartilage assessment in knee osteoarthritis using currently available MRI-based semiquantitative whole-organ scoring systems, and to provide an update on the risk factors for cartilage loss in knee osteoarthritis as assessed with these scoring systems.
EVALuna2:14483